Pengaruh Pembelajaran Tematik Terpadu Connected Terhadap Pembelajaran Matematika Siswa Sekolah Dasar - Fatimah Fatimah; Yanti Fitria; Yeni Erita (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This study aims to explore the effect of connected integrated thematic learning on mathematics learning for elementary school students. Qualitative methods are used in this study, with relevant data collection techniques. The research was conducted in an elementary school in an urban area, involving two classes that applied connected integrated thematic learning and two other classes that applied conventional learning. Data was collected through class observations, interviews with teachers, and analysis of documents related to curriculum and learning materials. The results of the study show that connected integrated thematic learning has a positive effect on elementary school students' mathematics learning. In connected integrated thematic learning, students are involved in projects that are integrated with mathematical content. They learn mathematics through the application of concepts and skills in contexts that are relevant to everyday life. This helps students understand mathematics better, because they can see the relationship between mathematics and the real world. In addition, connected integrated thematic learning also increases students' motivation and